Determinasi Islamic Service Quality (ISQ) dan Citra Lembaga terhadap Loyalitas Wali Murid pada Sekolah Dasar Islam (SDI) - Muhammad Durrin Ni'am; Zackyl Musthofa; Moh Mohlas; Hafidatun Nabila; Ida Kusumawati; Ittaqillah Haitsuma Kunta; Abu Hasan Agus (CV. Lentera Literasi Indonesia, 2026)
This study discusses the influence of Islamic Service Quality (ISQ) and institutional image on the loyalty of students' guardians in Islamic Elementary Schools (SDI). By using quantitative methods and multiple linear regression analysis, the results of the study show that the quality of service in religious teaching and a positive image of the institution have a great influence on the loyalty of students' guardians. Parents who are satisfied with religious teaching and assess the image of a good school tend to be more loyal. However, there are also parents who are dissatisfied with the available learning facilities and technology. These findings show the importance of maintaining a balance between ISQ and the image of the institution, as well as the need to improve educational facilities and technology to strengthen the loyalty of students' guardians. This research provides practical advice for SDI managers in designing strategies to improve service quality and build better relationships with parents, thereby supporting the sustainability and success of the school.